Economic evaluation of combined generation and storage solutions in low voltage Portuguese consumers - João Tomé Saraiva (2016)
This paper presents the results that were obtained in the scope of a consultancy study developed by INESC TEC for a Portuguese distribution network company to evaluate the interest of installing storage devices and PV panels in LV installations. We conducted simulations for consumers with annual demands of 5000 kWh (Type C consumers) and 7500 kWh (Type B consumers). In general, we concluded that the installation of storage devices is still of little economic interest given the current investment level and the tariffs paid to inject electricity in the networks. The largest NPV values were obtained when only installing PV panels in Type B consumers, the larger ones, and selling the surplus energy to the network.